Complicated Meckel's diverticulum: Presentation modes in adults. Issue 38 (September 2018) - Parvanescu, Alina; Bruzzi, Matthieu; Voron, Thibault; Tilly, Camille; Zinzindohoué, Franck; Chevallier, Jean-Marc; Gucci, Marco; Wind, Philippe; Berger, Anne; Douard, Richard
Abstract : Abstract: Complicated Meckel's diverticulum represents a common etiology of acute abdomen in children. However, this condition is less frequent in adults. We reviewed the records of adult patients who underwent the surgical removal of complicated Meckel's diverticulum between 2001 and 2017 at 2 tertiary French medical centers. We then analyzed the clinical characteristics, mode of presentation, and management for all patients. The Meckel's diverticulum was resected in 37 patients (24 males and 13 females). The mean patient age was 46.1 ± 21.4 years. The most common clinical presentations of complicated Meckel's diverticulum were diverticulitis (35.1%, n = 13), small-bowel obstruction (35.1%, n = 13), and gastrointestinal bleeding (29.8%, n = 11) (anemia, n = 1; hematochezia, n = 10). Age distribution was significantly different ( P  = .02) according to the 3 Meckel's diverticulum complications: patients with diverticulitis ( P  = .02) were statistically more frequently over 40 ( P  = .05), significantly older than patients with gastrointestinal bleeding who were more frequently <40 ( P  = .05). There was a preoperative diagnosis available for 15 of the 37 patients (40%). An exploratory laparoscopy was necessary to determine the cause of disease for the other 22 patients (60%). An intestinal resection was performed in 33 patients (89%) and diverticulectomy was performed in 4 patients (11%). There was heterotopic tissue found in only 6 patients (16%). Postoperative complications were as follows: 1 death by cardiac failure in a 92-year-old patient and 2 patients with postoperative wound infections. The follow-up time was 3 to 12 months. The correct diagnosis of complicated Meckel's diverticulum in adults is difficult due to the lack of specific clinical presentation. As a result, exploratory laparoscopy appears to play a central role in cases of acute abdomen with uncertain diagnosis.